PP45 Developing Recommendations to Improve the Effectiveness of Multidisciplinary Team Meetings for Patients with Chronic Diseases. (10th September 2013) - Nic a' Bháird, C; Wallace, I; Xanthopoulou, P; Barber, J; Clarke, A; Lanceley, A; Ardron, D; Harris, M; Blazeby, J; Ferlie, E; Gibbs, S; King, M; et al.
Abstract : Background: Multidisciplinary team meetings (MDMs) have been endorsed by the Department of Health as the core model for managing chronic diseases. It is believed that MDMs ensure higher quality decision making and improved outcomes. However, the evidence underpinning the development of MDMs is not strong and the degree to which MDMs have been absorbed into clinical practice varies widely across conditions and settings. We conducted a large mixed-methods study of multidisciplinary teams in chronic diseases to examine and explore determinants of effective decision making. We applied a transparent and explicit consensus development method to develop recommendations, based on our results, to improve MDM decision making and effectiveness. Methods: We collected qualitative and quantitative data from 12 multidisciplinary teams (gynaecological, skin and haematological cancers, mental health, memory clinics and heart failure). Data included non-participant observation of 370 MDMs and follow up of medical records, 53 interviews with healthcare professionals and 20 patient interviews. We triangulated these datasets to increase the internal validity and consistency of our findings. Over the course of successive analytic meetings we identified patterns of convergence to develop a coherent framework for understanding our findings. Based on this analysis we derived a series of potential recommendations for discussion and rating by an expert consensus development panel including policy makers, healthcare professionals and patient representatives. Results: Issues for discussion by the consensus panel included: whether or not patients should attend MDMs; how patient perspectives can be best represented; determining which patients, and indeed whether all patients should be included for discussion; suggestions for improvements in MDM processes, including the structure and co-ordination of MDMs; whether functions such as teaching and emotional support for team members have a valid role in the MDM, and if so, how best to incorporate them. The issue of how to incorporate multi-morbidity in disease specific MDMs was also considered. Conclusion: We have conducted the largest study of its kind in this area and the first to examine and compare MDMs for different chronic diseases. In addition, the use of a diverse range of qualitative and quantitative data allowed an unprecedented breadth and depth of data to be explored. This produced wide ranging, important and feasible recommendations to improve the effectiveness of MDMs which, the data suggest are generalisable to different patient groups.